Reconsidering the common ratio effect: The roles of compound independence, reduction, and coalescing - Ulrich Schmidt; Christian Seidl (Kiel Institute for the World Economy (IfW), 2014)
Common ratio effects should be ruled out if subjects' preferences satisfy compound independence, reduction of compound lotteries, and coalescing. In other words, at least one of these axioms should be violated in order to generate a common ratio effect. Relying on a simple experiment, we investigate which failure of these axioms is concomitant with the empirical observation of common ratio effects.We observe that compound independence and reduction of compound lotteries hold, whereas coalescing is systematically violated. This result provides support for theories which explain the common ratio effect by violations of coalescing (i.e., configural weight theory) instead of violations of compound independence (i.e., rank-dependent utility or cumulative prospect theory).
Keywords: C91; C44; D81; 330; common ratio effect; coalescing; reduction; compound independence; event splitting; branch splitting; isolation effect; Allais paradox